Impact on Pharmaceutical Industry due to Sudden Pandemic Attack (COVID-19) - Mishra, Sudhanshu; Sharma, Disha; Srivastava, Shobhit P.; Verma, Swati; Malviya, Rishabha (Coronaviruses, 2022)
The coronavirus disease (COVID-19) was first detected in Wuhan, China, in the month of December 2019. Further, in March 2020, the COVID-19 epidemic was described by the World Health Organisation (WHO) as a global pandemic. COVID-19 quickly spread around the world in the following months, affecting about 2.5 million individuals by April 2020. World markets, including the pharmaceutical industry, were devastated by this pandemic. Although no specific solution for this emerging infectious disease is currently available, the pharmaceutical industry is helping policymakers meet unmet COVID-19 desires, ranging from research and advancement initiatives on possible prevention methods to the management of the supply chain of drugs in times of crisis. Changes in demand, commodity shortages, contact adjustments, etc., are hindering developments in the mechanism of technology, research and development and are putting an impact on the health market of COVID-19. Other implications of COVID-19 on the physical condition and pharmaceutical market may include acceptance delays, heading to self-sufficiency in the delivery chain, etc. In addition, the pharmaceutical markets are battling to sustain natural consumer flows, as the latest pandemic has had an effect on access to essential drugs at reasonable rates, which is the key priority of all pharmaceutical systems.
Keywords: pharmaceutical industry